ANALISIS PENGARUH VARIABEL MONETER INDONESIA DAN INDEKS SAHAM NEGARA LAIN TERHADAP IHSG - Pasaribu, Christian Noel; Munawar Ismail (Contemporary Studies in Economic, Finance and Banking, 2024)
This study aims to determine the effect of Indonesian monetary variables and other countries' stock indices on the Composite Stock Price Index (JCI). The data used is monthly time series data from January 2020 to December 2023. The method used in this study is the Vector Error Correction Model (VECM) method which is determined from the results of the stationarity test, lag determination, cointegration test. The independent variables used include monetary variables (inflation and exchange rates) and stock indices of other countries (nikkei 225 and Dow Jones Industrial Average /DJIA). The dependent variable used is the JCI. The results showed that all monetary variables (inflation and exchange rates) had no influence in the short term, while in the long term both monetary variables had a negative effect on the JCI. Meanwhile, other countries' stock index variables, namely the DJIA, negatively affect the JCI both in the short and long term. Nikkei 225 has a positive short term effect on JCI, while in the long term nikkei 225 has no effect on JCI.